2015
DOI: 10.1021/jf505581n
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Biochemical Activities of N-(2-Carboxyethyl)chitosan from Squid Pens

Abstract: Chitosan was prepared by alkaline N-deacetylation of β-chitin from squid pens, and N-carboxyethylated derivatives (N-CECS) with different degrees of substitution (DS) were synthesized. The carboxyethylation of the polysaccharide was identified by Fourier transform infrared, (1)H and (13)C nuclear magnetic resonance (NMR), and X-ray diffraction analyses. The DS of the derivatives was calculated by (1)H NMR and elemental analysis. All three N-CECS samples showed good water solubility at pH > 6.5. The antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Not only could hydroxyl groups of the polysaccharides be easily oxidized under the aerobic condition, but also the ABTS radicals scavenging capacities of the polysaccharides dried in oxygen environment were obviously decreased due to the oxidation of the hydroxyl groups[ 26 ]. In addition, the reaction of ABTS radicals with the active hydroxyl groups could be inhibited by the hydrogen bonds formed between intermolecules or intramolecules of the polysaccharides [ 50 ]. Compared with freeze-drying or rotary evaporation-drying process, CGP was dehydrated by spray-drying under the aerobic condition.…”
Section: Resultsmentioning
confidence: 99%
“…Not only could hydroxyl groups of the polysaccharides be easily oxidized under the aerobic condition, but also the ABTS radicals scavenging capacities of the polysaccharides dried in oxygen environment were obviously decreased due to the oxidation of the hydroxyl groups[ 26 ]. In addition, the reaction of ABTS radicals with the active hydroxyl groups could be inhibited by the hydrogen bonds formed between intermolecules or intramolecules of the polysaccharides [ 50 ]. Compared with freeze-drying or rotary evaporation-drying process, CGP was dehydrated by spray-drying under the aerobic condition.…”
Section: Resultsmentioning
confidence: 99%
“…The scavenging ability of N -CESC against superoxide radicals showed a good correlation with the degree of substitution and concentration of N -CESC. The data suggested that N -CESC can be utilized to produce chitosan derivatives with good biochemical characteristics in vitro [ 75 ]. Graft chitosan derivatives with low grafting percentages, produced by graft copolymerization of methacrylic acid sodium and acrylic acid sodium onto the etherification product of chitosan-carboxymethyl chitosan, exhibit a relatively low 50% inhibition concentration (IC 50 ) for their radical scavenging activity, which could be attributed to their different contents of hydroxyl and amino groups in the polymer chains [ 76 ].…”
Section: Bioactivities Of Chitosanmentioning
confidence: 99%
“… Scavenging effects of N -CECS with different degrees of substitution toward ABTS radicals. Reprinted with permission from [ 75 ] Copyright (2015) American Chemical Society. …”
Section: Bioactivities Of Chitosanmentioning
confidence: 99%
“…One possible means of addressing this challenge involves chitosan, which is the product of chitin deacetylation under alkaline conditions. Chitosan is a linear polysaccharide containing various proportions of GlcN [ 3 ]. It has applications in nutritional [ 4 ], agricultural [ 5 ], and medical areas [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%